Comercio internacional Colombia - Perú: una perspectiva empresarial desde la integración económica - García Suárez, Giovanna (2022)
In 30 years of commercial relations between Colombia and Peru within the framework of their different integration processes, this article aimed to analyze the Colombian companies that boost bilateral trade with Peru. The study reveals the companies and the main goods traded, the study was developed from the theoretical perspective of economic integration and the concept of South-South trade, through a predominantly quantitative method, with 300,692 data obtained from the interface of the National Statistical System (SEN) fed by the Tax and Customs Directorate Nationals (DIAN) during the last 5 years, 24,651 export operations and 18,305 import operations were obtained. Within the findings, the Colombian companies that export the most, those that import the most, and those with the highest volume of trade are categorized. The industry with the highest business participation is the hygiene and personal care sector, which ranks 5 companies out of the 10 with the highest commercial volume with significant exchanges in essential oils, chemical preparations, plastic, and paper manufactures. Regarding their size, it was found that 100% They are large multinational companies, with more than 50 years in the market. Of the 10 most representative companies: 2 are Colombian, 2 Peruvian, 4 American and 2 European